2005
DOI: 10.1111/j.1468-3083.2005.01072.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects and side‐effects of spironolactone therapy in women with acne

Abstract: Spironolactone is a safe and effective medication for women with acne vulgaris. Although its side-effects seem to be high, they are in the majority of cases not a reason to stop treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(35 citation statements)
references
References 12 publications
1
31
0
3
Order By: Relevance
“…Yemisci et al (2005) performed a similar study and demonstrated an 85% response rate with significant improvements in acne for responders. In another study on the effects of treatment with topical spironolactone, 78 patients were enrolled in a randomized, double-blind, placebo controlled trial.…”
Section: Spironolactonementioning
confidence: 86%
“…Yemisci et al (2005) performed a similar study and demonstrated an 85% response rate with significant improvements in acne for responders. In another study on the effects of treatment with topical spironolactone, 78 patients were enrolled in a randomized, double-blind, placebo controlled trial.…”
Section: Spironolactonementioning
confidence: 86%
“…To date, there have been 4 small-scale clinical studies, 6-9 each fewer than 100 patients, that have measured serum potassium as a secondary outcome in patients taking spironolactone for acne. Three studies [6][7][8] yielded zero cases of hyperkalemia, and one study 9 showed a 13.7% rate of mild hyperkalemia, which was defined as a serum potassium measurement of 4.8 to 5.3 mEq/L (to convert potassium level to millimoles per liter, multiply by 1.0). Although the US Food and Drug Administration recommends frequent potassium monitoring in patients taking spironolactone, it is unclear whether this guideline is applicable to healthy patients taking spironolactone for acne.…”
mentioning
confidence: 99%
“…Furthermore, spironolactone causes a decrease in plasma testosterone and an increase in estradiol by altering the peripheral metabolism of testosterone [117]. In fact, spironolactone has been shown to be useful in conditions of excess androgen, such as hirsutism [118], polycystic ovary syndrome [119] and acne vulgaris [120].…”
Section: Side Effectsmentioning
confidence: 98%